2012
DOI: 10.1111/j.1365-2958.2012.08186.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of archaella expression by the FHA and von Willebrand domain‐containing proteins ArnA and ArnB in Sulfolobus acidocaldarius

Abstract: The ability of microorganisms to sense and respond to sudden changes in their environment is often based on regulatory systems comprising reversible protein phosphorylation. The archaellum (former: archaeal flagellum) is used for motility in Archaea and therefore functionally analogous to the bacterial flagellum. In contrast with archaellum-mediated movement in certain members of the Euryarchaeota, this process, including its regulation, remains poorly studied in crenarchaeal organisms like Sulfolobus species.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(132 citation statements)
references
References 32 publications
10
120
0
Order By: Relevance
“…However, the physiological function of this cascade was not elucidated until Reimann et al. (2012) showed that in S. acidocaldarius a regulatory system consisting of the homolog of ST0829, ArnA and various other proteins regulates expression of the motility structure, the archaellum. In S. acidocaldarius , an operon consisting of seven genes, which are expressed from two promoters encodes for the archaellum (Fig.…”
Section: Ser Thr and Tyr Phosphorylation In Archaeamentioning
confidence: 99%
“…However, the physiological function of this cascade was not elucidated until Reimann et al. (2012) showed that in S. acidocaldarius a regulatory system consisting of the homolog of ST0829, ArnA and various other proteins regulates expression of the motility structure, the archaellum. In S. acidocaldarius , an operon consisting of seven genes, which are expressed from two promoters encodes for the archaellum (Fig.…”
Section: Ser Thr and Tyr Phosphorylation In Archaeamentioning
confidence: 99%
“…However, distinct PilB and PilC paralogues are required for archaeal type IV pilus and flagella biosynthesis (Albers and Pohlschroder, 2009;Ghosh and Albers, 2011;Lassak et al, 2012). Consistent with having unique biosynthesis machineries, it has recently been shown that the transcriptional regulation of archaeal flagella and pili expression within biofilms is, as in bacteria, inversely related (Reimann et al, 2012;Lassak et al, 2013;Orell et al, 2013b).…”
Section: Introductionmentioning
confidence: 97%
“…Furthermore, the first signal transduction pathway involved in archaella expression mediated by reversible protein phosphorylation was discovered in Sul. acidocaldarius (429,435) and Sul. tokodaii (436).…”
Section: Regulation At the Protein Levelmentioning
confidence: 99%